A polymer composite and its preparation method and application
By adding nanoparticles A and B with specific particle size and mass ratio to the polymer powder, polymer composites with excellent fluidity, permeability and high temperature stability are prepared, which solves the problems of poor fluidity of existing polymer powders and reduced fluidity at high temperatures.
Patent Information
- Application Number
- CN202111014660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-08-31
AI Technical Summary
The existing polymer powder has poor fluidity and decreases in fluidity at high temperatures, which limits its application range.
Nanoparticles A and nanoparticles B with a specific mass ratio are mixed with polymer powder, and the particle sizes of nanoparticles A and B are between 5-50nm and 50-600nm respectively. The polymer composite is prepared by stirring, mixing and screening to improve its fluidity, permeability and high temperature stability.
It significantly improves the fluidity and permeability of polymer composites and maintains stability at high temperatures. It is suitable for powder coatings and 3D printing and other fields.
Smart Images

Figure CN115725170B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a polymer composite and a preparation method and application thereof. Background Art
[0002] Polymer materials refer to high molecular weight compounds composed of many identical, simple structural units repeatedly connected by covalent bonds. Polymer powders are fine chemicals with a certain particle size and distribution and a certain particle morphology prepared by chemical or physical methods. Polymer powders are widely used in powder coatings, 3D printing, cosmetics, additives, medicine and other fields.
[0003] Although polymer powders can be prepared by chemical synthesis, such as suspension polymerization or emulsion polymerization, the preparation process is complicated and the types of polymers are also limited. Most of them can only prepare styrene or acrylic (ester) polymers. At present, the main means of obtaining polymer powders is still mechanical crushing, which has the advantages of simple process and continuous production, but the prepared particles have a disorderly shape and a wide particle size distribution.
[0004] The above two methods are commonly used methods for preparing polymer powders, but the powders obtained by these two methods are irregular in shape and have poor fluidity, and good fluidity is the key to the application of polymer powders. At present, the methods for improving the fluidity of polymer powders are mainly to reduce the interfacial force of particles (for example, adding a flow aid or coating the polymer) and reduce rolling resistance (for example, shaping the polymer particles, such as spherical). In addition, due to the limited heat resistance of polymers, when the use temperature increases, the powder fluidity decreases significantly, limiting the scope of application. In the first method, the mixing process of the flow aid can be carried out in any suitable mixing equipment, including a fluidized bed, and one or more various drums or mixers equipped with a rotating shaft.
[0005] CN1102954C discloses a method for preparing a granular detergent composition, which method includes the steps of adding a powder flowability aid of percarbonate and partially hydrated crystalline sodium aluminosilicate with an average particle size in the range of 250-900 microns to granular detergent powder particles.
[0006] CN109929242A discloses a nylon polymer powder heat-absorbing material and a preparation method thereof. The preparation method disclosed in the invention comprises the following steps: adding nylon raw material, molecular weight regulator and deionized water into a polymerization kettle, adding heat medium after the pressure in the kettle is relieved to normal pressure, stirring and drawing and cutting to obtain nylon heat medium pellets; adding nylon heat medium pellets into a post-condensation barrel, heating and vacuuming and stirring to obtain nylon heat medium condensation pellets; using a deep cold crushing process to obtain nylon heat medium powder material; adding 20 parts of nylon heat medium powder material and 0.1-2 parts of carbon black into a stirring barrel for high-speed stirring to obtain nylon carbon black mixed powder material; adding nylon carbon black mixed powder material, flow aid and 80 parts of nylon heat medium powder material into a powder mixing barrel, stirring at high speed and then screening to obtain nylon polymer powder heat-absorbing material. The disclosed method enables nylon polymer powder to be applied to fiber laser sintering, and the surface quality and mechanical properties of the product are good.
[0007] CN108727814A discloses a composite nylon powder material for selective laser sintering and a preparation method thereof. The composite nylon powder material disclosed in the invention comprises the following components in weight ratio: 30-70 parts of nylon resin powder; 30-50 parts of hollow glass microspheres; 0-20 parts of glass fiber; 0.2-2 parts of coupling agent; 0.1-1.5 parts of flow aid; 0.2-2 parts of antioxidant. The modified glass fiber and hollow glass microsphere disclosed in the invention are added to the nylon resin powder. Compared with the simple addition of glass fiber, the nylon composite powder with hollow glass microspheres and glass fiber added at the same time has better fluidity, better powder spreading effect, and higher strength modulus of sintered parts. The nylon composite material of hollow glass microspheres and glass fiber expands the application field of nylon.
[0008] Currently, the improvement of polymer fluidity by reducing particle interface forces and rolling resistance is limited. Therefore, it is crucial to develop a polymer material with excellent fluidity. Summary of the invention
[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a polymer composite and a preparation method and application thereof, wherein the polymer composite has excellent fluidity, permeability and high temperature stability.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a polymer composite, wherein the polymer composite comprises the following components in parts by weight: 100 parts of polymer powder, 0.1-3 parts of nanoparticles A and 0.05-1.5 parts of nanoparticles B;
[0012] Among them, the particle size of nanoparticle A is smaller than that of nanoparticle B;
[0013] The mass ratio of the nanoparticles A and the nanoparticles B is (1-9):1, wherein 1-9 can be 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, etc.
[0014] The polymer composite of the present invention uses nanoparticles A and nanoparticles B in a specific mass ratio as flow agents for polymer powders. The two nanoparticles act synergistically and are coated on the polymer powders to reduce the friction and force on the surface of the particles, thereby improving the flowability, permeability and stability of the polymer powders at high temperatures.
[0015] The weight proportion of the nanoparticles A is 0.1-3 parts, for example, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, etc.
[0016] The weight proportion of the nanoparticles B is 0.05-1.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, etc.
[0017] Preferably, the mass ratio of the nanoparticles A and nanoparticles B is (1.5-4):1, wherein 1.5-4 can be 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, etc.
[0018] The mass ratio of the nanoparticles A to the nanoparticles B of the present invention is preferably (1.5-4):1. When the mass ratio is within this range, the fluidity and high-temperature stability of the polymer composite obtained are better.
[0019] Preferably, the particle size of the nanoparticle A is 5-50 nm, for example 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 42 nm, 45 nm, 48 nm, etc., preferably 5-30 nm.
[0020] The particle size of the nanoparticles A of the present invention is preferably 5-30 nm, because nanoparticles with small particle sizes can form a denser coating on the surface of the polymer, thereby reducing the interaction force between the particles.
[0021] Preferably, the particle size of the nanoparticles B is 50-600 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, etc., preferably 50-300 nm.
[0022] The particle size of the nanoparticles B of the present invention is preferably 50-300 nm, because nanoparticles with larger particle sizes form rolling friction and barrier effects on the polymer surface, reducing the interaction force between particles.
[0023] Preferably, the median particle size of the polymer powder is 5-500 μm, for example, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, etc., preferably 10-300 μm, more preferably 50-150 μm.
[0024] Preferably, the polymer powder comprises thermoplastic polymer powder and / or thermosetting polymer powder.
[0025] Preferably, the polymer powder comprises a thermoplastic polymer powder.
[0026] Preferably, the thermoplastic polymer powder comprises any one of thermoplastic elastomer, polyamide, polyolefin, polymethacrylate, polycarbonate or polystyrene, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of thermoplastic elastomer and polyamide, a combination of polyolefin, polymethacrylate and polycarbonate, a combination of polyamide, polyolefin, polymethacrylate, polycarbonate and polystyrene, etc.
[0027] Preferably, the nanoparticle A comprises any one of nano-silicon dioxide, nano-titanium dioxide or nano-silicon carbide, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of nano-silicon dioxide and nano-titanium dioxide, a combination of nano-titanium dioxide and nano-silicon carbide, a combination of nano-silicon dioxide, nano-titanium dioxide and nano-silicon carbide, and the like.
[0028] Preferably, the nanoparticles B include any one of nano-silicon dioxide, nano-titanium dioxide, nano-silicon carbide, nano-aluminum oxide, talc, magnesium stearate or magnesium oxide, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of nano-silicon dioxide and nano-titanium dioxide, a combination of nano-titanium dioxide, nano-silicon carbide and nano-aluminum oxide, and a combination of nano-aluminum oxide, talc, magnesium stearate and magnesium oxide.
[0029] In a second aspect, the present invention provides a method for preparing the polymer composite according to the first aspect, the preparation method comprising the following steps:
[0030] After the polymer powder and the nanoparticles A are stirred and mixed for the first time, the mixed raw materials are stirred and mixed with the nanoparticles B for the second time, and sieved to obtain the polymer composite.
[0031] In the process of preparing the polymer composite of the present invention, the polymer powder is preferentially mixed with the nanoparticles A with a smaller particle size, so that the nanoparticles A can be better and densely coated on the particle surface. However, the nanoparticles B have a larger particle size. If the nanoparticles B are mixed first, the coverage of the small-size nanoparticles on the polymer powder surface will be affected.
[0032] Preferably, the first stirring and mixing time is 1-15 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, etc., preferably 1-3 min.
[0033] Preferably, the second stirring and mixing time is 1-6 min, for example, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, 5.5 min, etc., preferably 1-2 min.
[0034] The stirring and mixing described in the present invention is continuous stirring and mixing. If the mixing time is insufficient, the polymer powder and the nanoparticles cannot be evenly mixed; if the mixing time is too long, the nanoparticles will be lost and embedded, thereby losing the effect of the composite nanoparticles.
[0035] Preferably, the screening is performed through a sieve.
[0036] Preferably, the mesh size of the sieve is 50-300 mesh, such as 60 mesh, 80 mesh, 100 mesh, 120 mesh, 140 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 240 mesh, 260 mesh, etc. The mesh size of the sieve is 50-300 mesh, and the particle size of the particles passing through the sieve is 30-500 mesh.
[0037] As a preferred technical solution, the preparation method comprises the following steps:
[0038] The polymer powder and nanoparticles A are stirred and mixed for the first time for 1-15 minutes, and then the mixed raw materials are stirred and mixed with nanoparticles B for the second time for 1-6 minutes, and finally sieved with a sieve with a mesh size of 50-300 to obtain the polymer composite.
[0039] In a third aspect, the present invention provides a use of the polymer composite described in the first aspect in powder coating or 3D printing.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The small-size and large-size nanoparticles used in the present invention are compounded in a specific ratio, and the two act synergistically as a flow agent for the polymer powder, so that the polymer composite has excellent fluidity, permeability and high-temperature stability. Taking the polymer powder as thermoplastic polyurethane as an example, the SE flow energy of the polymer composite is below 7.75 mJ / g, the FRI is below 1.35, and the permeability is above 4.11 mbar. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a scanning electron microscope image of the polymer composite described in Example 1;
[0043] Figure 2 is a scanning electron microscope image of the polymer composite described in Example 1 after being heated at 100° C.;
[0044] Figure 3 is a scanning electron microscope image of the polymer composite described in Example 2;
[0045] Figure 4 is a scanning electron microscope image of the polymer composite described in Example 2 after being heated at 135° C.;
[0046] Figure 5 is a scanning electron micrograph of the polymer composite described in Example 3;
[0047] Figure 6 is a scanning electron micrograph of the polymer composite described in Example 4;
[0048] Figure 7 is a scanning electron micrograph of the polymer composite described in Example 6;
[0049] Figure 8 is a scanning electron micrograph of the polymer composite described in Example 8;
[0050] Fig. 9 is a scanning electron microscope image of the polymer composite described in Comparative Example 1;
[0051] Fig.10 is a scanning electron microscope image of the polymer composite of Comparative Example 1 after being heated at 100° C.;
[0052] Fig.11 This is a scanning electron microscope image of the polymer composite described in Comparative Example 2. DETAILED DESCRIPTION
[0053] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Example 1
[0055] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 0.3 parts of nanoparticles A and 0.13 parts of nanoparticles B;
[0056] The polymer powder: cryogenically crushed thermoplastic polyurethane, with a median particle size of 65 μm and a hardness of Shore A 90, purchased from Wanhua Chemical Group Co., Ltd., with a brand name of WHT-1490IV;
[0057] Nanoparticle A: nanosilicon dioxide, particle size 12nm;
[0058] Nanoparticle B: nano-silicon dioxide, particle size is 50nm.
[0059] The preparation method of the polymer composite comprises the following steps:
[0060] The polymer powder and the nanoparticles A were mixed for the first time for 2 minutes, and then the mixed raw materials were mixed with the nanoparticles B for a second time for 1 minute. Finally, the mixture was sieved with a 50-mesh sieve to obtain the polymer composite.
[0061] Example 2
[0062] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 0.5 parts of nanoparticles A and 0.33 parts of nanoparticles B;
[0063] The polymer powder: cryogenically crushed polypropylene, with a median particle size of 50 μm, purchased from Wanhua Chemical Group Co., Ltd., with a brand name of WANFAB GP1000;
[0064] Nanoparticle A: nano silicon carbide, particle size 5nm;
[0065] Nanoparticle B: nano-aluminum oxide, particle size is 80nm.
[0066] The preparation method of the polymer composite comprises the following steps:
[0067] The polymer powder and the nanoparticles A were mixed for the first time for 3 minutes, and then the mixed raw materials were mixed with the nanoparticles B for the second time for 2 minutes. Finally, the mixture was sieved with a 70-mesh sieve to obtain the polymer composite.
[0068] Example 3
[0069] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 3 parts of nanoparticles A and 0.75 parts of nanoparticles B;
[0070] The polymer powder is a phenolic resin that has been cryogenically crushed, with a median particle size of 5 μm, and the raw material grade is 2123 phenolic resin;
[0071] Nanoparticle A: nano-titanium dioxide, particle size 5nm;
[0072] Nanoparticle B: Nano-silicon carbide, with a particle size of 50 nm.
[0073] The preparation method of the polymer composite comprises the following steps:
[0074] The polymer powder and the nanoparticles A were mixed for the first time for 15 minutes, and then the mixed raw materials were mixed with the nanoparticles B for a second time for 6 minutes. Finally, the mixture was sieved with a 300-mesh sieve to obtain the polymer composite.
[0075] Example 4
[0076] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 0.2 parts of nanoparticles A and 0.06 parts of nanoparticles B;
[0077] The polymer powder is a thermoplastic polyurethane after cryogenic grinding, with a median particle size of 500 μm and a hardness of Shore A90. The raw material is purchased from Wanhua Chemical Group Co., Ltd. and the brand is WHT-1490IV.
[0078] Nanoparticle A: nanosilicon dioxide, particle size 50nm;
[0079] Nanoparticle B: talc powder, particle size is 600 nm.
[0080] The preparation method of the polymer composite comprises the following steps:
[0081] The polymer powder and the nanoparticles A were mixed for the first time for 1 minute, and then the mixed raw materials were mixed with the nanoparticles B for the second time for 1 minute. Finally, the mixture was sieved with a 50-mesh sieve to obtain the polymer composite.
[0082] Example 5
[0083] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 0.1 parts of nanoparticles A and 0.05 parts of nanoparticles B;
[0084] The polymer powder is a thermoplastic polyurethane after cryogenic grinding, with a median particle size of 150 μm and a hardness of Shore A90. The raw material is purchased from Wanhua Chemical Group Co., Ltd. and the brand is WHT-1490IV.
[0085] Nanoparticle A: nano-titanium dioxide, particle size 30nm;
[0086] Nanoparticle B: talc powder, particle size is 300 nm.
[0087] The preparation method of the polymer composite comprises the following steps:
[0088] The polymer powder and the nanoparticles A were mixed for the first time for 1 minute, and then the mixed raw materials were mixed with the nanoparticles B for the second time for 2 minutes. Finally, the mixture was sieved with a 60-mesh sieve to obtain the polymer composite.
[0089] Example 6
[0090] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 2 parts of nanoparticles A and 0.75 parts of nanoparticles B;
[0091] The polymer powder is a thermoplastic polyurethane after cryogenic grinding, with a median particle size of 10 μm and a hardness of Shore A 90. The raw material is purchased from Wanhua Chemical Group Co., Ltd. and the brand is WHT-1490IV.
[0092] Nanoparticle A: nano silicon carbide, particle size 5nm;
[0093] Nanoparticle B: nano-silicon dioxide, particle size is 50nm.
[0094] The preparation method of the polymer composite comprises the following steps:
[0095] The polymer powder and the nanoparticles A were mixed for the first time for 1.5 minutes, and then the mixed raw materials were mixed with the nanoparticles B for a second time for 1 minute. Finally, the mixture was sieved with a 300-mesh sieve to obtain the polymer composite.
[0096] Example 7
[0097] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 2 parts of nanoparticles A and 0.5 parts of nanoparticles B;
[0098] The polymer powder is a thermoplastic polyurethane after cryogenic grinding, with a median particle size of 300 μm and a hardness of Shore A90. The raw material is purchased from Wanhua Chemical Group Co., Ltd. and the brand is WHT-1490IV.
[0099] Nanoparticle A: 1 part of nano-silicon dioxide, particle size 35nm, 1 part of nano-titanium dioxide, particle size 35nm;
[0100] Nanoparticle B: 0.25 parts of nano silicon carbide with a particle size of 150 nm, and 0.25 parts of nano aluminum oxide with a particle size of 150 nm.
[0101] The preparation method of the polymer composite comprises the following steps:
[0102] The polymer powder and the nanoparticles A were mixed for the first time for 2 minutes, and then the mixed raw materials were mixed with the nanoparticles B for the second time for 2 minutes. Finally, the mixture was sieved with a 50-mesh sieve to obtain the polymer composite.
[0103] Example 8
[0104] This embodiment provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder, 1 part of nanoparticles A and 0.3 parts of nanoparticles B;
[0105] The polymer powder: cryogenically crushed polypropylene, with a median particle size of 80 μm, purchased from Wanhua Chemical Group Co., Ltd., with a brand name of WANFAB GP1000;
[0106] Nanoparticle A: 0.5 parts of nano-silicon dioxide, with a particle size of 15 nm, and 0.5 parts of nano-silicon carbide, with a particle size of 15 nm;
[0107] Nanoparticle B: 0.15 parts of nano-silicon carbide with a particle size of 100 nm, and 0.15 parts of nano-silicon dioxide with a particle size of 100 nm.
[0108] The preparation method of the polymer composite comprises the following steps:
[0109] The polymer powder and the nanoparticles A were mixed for the first time for 2 minutes, and then the mixed raw materials were mixed with the nanoparticles B for the second time for 3 minutes. Finally, the mixture was sieved with a 60-mesh sieve to obtain the polymer composite.
[0110] Examples 9-12
[0111] The difference between Examples 9-12 and Example 1 is that the mass ratio of nanoparticles A to nanoparticles B is different, and the total mass of nanoparticles A and nanoparticles B is 0.6 parts;
[0112] In Examples 9-12, the mass ratios of nanoparticles A to nanoparticles B are 9:1 (Example 9), 1:1 (Example 10), 4:1 (Example 11) and 1.5:1 (Example 12), respectively, and the rest are the same as in Example 1.
[0113] Examples 13-16
[0114] The difference between Examples 13-16 and Example 1 is that the particle sizes of nanoparticles A are 5 nm (Example 13), 50 nm (Example 14), 3 nm (Example 15) and 60 nm (Example 16), respectively, and the rest are the same as Example 1.
[0115] Examples 17-19
[0116] The difference between Examples 17-19 and Example 1 is that the particle sizes of nanoparticles B are 600 nm (Example 17), 30 nm (Example 18) and 700 nm (Example 19), respectively, and the rest are the same as Example 1.
[0117] Comparative Example 1
[0118] This comparative example provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder and 0.5 parts of small-size nanoparticles;
[0119] The polymer powder is a thermoplastic polyurethane after cryogenic grinding, with a median particle size of 60 μm and a hardness of Shore A 90. The raw material is purchased from Wanhua Chemical Group Co., Ltd. and the brand is WHT-1490IV;
[0120] Small-size nanoparticles: Nano-silicon dioxide, particle size is 15nm.
[0121] The preparation method of the polymer composite comprises the following steps:
[0122] The polymer powder and the small-size nanoparticles were mixed for 2 minutes and then sieved with a 50-mesh sieve to obtain the polymer composite.
[0123] Comparative Example 2
[0124] This comparative example provides a polymer composite, which is composed of the following components in parts by weight: 100 parts of polymer powder and 0.7 parts of large-diameter nanoparticles;
[0125] The polymer powder: cryogenically crushed thermoplastic polyurethane, with a median particle size of 80 μm and a hardness of Shore A 90, purchased from Wanhua Chemical Group Co., Ltd., with a brand name of WHT-1490IV;
[0126] Large-size nanoparticles: Nano-silicon dioxide, with a particle size of 100nm.
[0127] The preparation method of the polymer composite comprises the following steps:
[0128] The polymer powder and the large-size nanoparticles were mixed for 3 minutes and then sieved with a 80-mesh sieve to obtain the polymer composite.
[0129] Comparative Examples 3-4
[0130] The difference between Comparative Example 3-4 and Example 1 is that the mass ratio of nanoparticles A to nanoparticles B is different, and the total mass of nanoparticles A and nanoparticles B is 0.6 parts;
[0131] In Comparative Examples 3-4, the mass ratios of nanoparticles A to nanoparticles B are 10:1 and 1:4, respectively, and the rest are the same as in Example 1.
[0132] Performance Test:
[0133] The polymer composites described in Examples 1-19 and Comparative Examples 1-4 were tested as follows:
[0134] (1) Flow properties: After the sample is fully dried, it is measured using a Freeman FT4 powder rheometer. After opening the test software, the required test method "stability and variable flow rate" is selected to test the flowability. The test results include flow activation energy. "permeability" is used to test the air permeability of 1 to 15 kPa. The test results include a pressure drop of 1 to 15 kPa. Finally, data processing is performed;
[0135] (2) Bulk density: Use the BT-1000 powder comprehensive property tester to measure. Clean the density container and keep the inside dry. Then adjust the density meter to a horizontal level with the funnel opening 40 mm from the upper edge of the density cup. Open the powder comprehensive property tester and install a 100 m bulk density container.
[0136] Weigh 100g of powder sample and pour it into the funnel above the tester, and block the discharge port of the funnel;
[0137] Quickly open the discharge port of the funnel to allow the sample in the funnel to fall vertically into the density container in a natural state. Use a shovel to scrape off the excess sample on the top of the density cup. Tap the density cup to fix the sample. Record the powder mass M1 in the container and the bulk density ρ (g / cm 3 )=M1 / 100;.
[0138] The test was performed multiple times to ensure the repeatability of the results. The test results are summarized in Table 1.
[0139] Table 1
[0140]
[0141]
[0142]
[0143] From the analysis of the data in Table 1, it can be seen that, taking the polymer powder as thermoplastic polyurethane as an example, the SE flow energy of the polymer composite is below 7.75 mJ / g, the FRI is below 1.35, and the permeability is above 4.11 mbar. The small-size and large-size nanoparticles used in the polymer composite of the present invention act synergistically as the flow agent of the polymer powder. The cohesive characteristic indexes FRI and SE flow energy of the polymer composite formed by the mixture of the three are low, indicating that the composite use of small-size and large-size nanoparticles has the effect of reducing the flow resistance of the polymer powder; and the air permeability pressure drop of the polymer composite is significantly higher, indicating that the powder is more densely packed and there are fewer gaps between the particles, which is consistent with the result of the packing density. The BFE flow energy is a comprehensive characterization of the packing density and the cohesive characteristics of the powder. The powder with large packing density and large cohesive characteristics has a higher energy required for the powder rheometer paddle to push, and the BFE also shows an increasing trend. Therefore, the polymer composite of the present invention has excellent fluidity and permeability.
[0144] From the analysis of Comparative Examples 1-2 and Example 1, it can be seen that although the bulk density in Comparative Example 2 is relatively large due to the selection of large-particle powder, since the bulk density is not as sensitive to fluidity as it is to particle size, it can be inferred that the performance of Comparative Examples 1-2 is still inferior to Example 1, proving that the synergistic combination of nanoparticles A and nanoparticles B can be used as a flow agent for polymer powder to form a polymer composite with excellent fluidity and high-temperature stability.
[0145] Analysis of Comparative Examples 3-4 and Examples 9-10 shows that the performance of Comparative Examples 3-4 is not as good as that of Examples 9-10, proving that the performance of the polymer composite obtained when the mass ratio of the nanoparticles A to the nanoparticles B is in the range of (1-9):1 is better.
[0146] Analysis of Examples 9-12 shows that the performance of Examples 9-10 is not as good as that of Examples 11-12, which proves that the mass ratio of the nanoparticles A to the nanoparticles B is preferably (1.5-4):1, and the performance of the resulting polymer composite is better.
[0147] Analysis of Examples 13-16 shows that the performance of Examples 15-16 is not as good as that of Examples 13-14, proving that the particle size of nanoparticle A can better cooperate with nanoparticle B to improve the performance of the polymer composite when it is in the range of 5-50 nm.
[0148] Analysis of Examples 17-19 and Example 1 shows that the performance of Examples 18-19 is not as good as that of Examples 1 and 17, proving that the particle size of nanoparticles B can better cooperate with nanoparticles A to improve the performance of the polymer composite when it is in the range of 50-600 nm.
[0149] contrast Figure 1 and Figure 2 It can be seen that Figure 1In the figure, nanoparticles B and nanoparticles A are uniformly distributed in the polymer powder matrix; Figure 2 After heating at 100°C, nanoparticles B and nanoparticles A are still evenly distributed in the polymer powder matrix without loss or embedding, which proves that the polymer composite of the present invention has excellent high temperature stability. Figure 3 and Figure 4 with similar results.
[0150] contrast Fig. 9 and Fig.10 It can be seen that Fig. 9 The single type of nanoparticles in the polymer powder matrix are uniformly distributed, but after heating, Fig.10 The nanoparticles in the polymer composites showed obvious entrapment and loss, which affected the heat resistance and high-temperature fluidity of the polymer composites.
[0151] Therefore, the nanoparticles A and nanoparticles B are compounded in a specific ratio and mixed with the polymer powder to form a polymer composite having excellent fluidity and high-temperature thermal stability.
[0152] analyze Figure 5-Figure 8 It can be seen that by properly adjusting the particle size and type of nanoparticles A, nanoparticles B and polymer powder, the obtained polymer composite has excellent fluidity and high temperature thermal stability. Although the present invention does not provide a scanning electron microscope image after high temperature heating, it is inferred from the results of Examples 1-2 and Comparative Example 1 that Examples 3-4, 6, and 8 also have similar results, that is, the polymer composite formed by mixing nanoparticles A and nanoparticles B in a specific ratio with the polymer powder has excellent fluidity and high temperature thermal stability; Fig.11 Although the nanoparticles are evenly distributed, it can be predicted that the results are similar to those of Comparative Example 1, that is, nanoparticles of a single particle size have limited improvement on the performance of the polymer powder, especially high temperature stability and fluidity.
[0153] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polymer composite, characterized in that The polymer composite comprises the following components in parts by weight: 100 parts of polymer powder, 0.1-3 parts of nanoparticles A and 0.05-1.5 parts of nanoparticles B; Among them, the particle size of nanoparticle A is smaller than that of nanoparticle B; The mass ratio of the nanoparticles A and B is (1-9):1; The particle size of the nanoparticle A is 5-50 nm; The particle size of the nanoparticle B is 50-600 nm; The median particle size of the polymer powder is 5-500 μm; The nanoparticles A include any one of nano-silicon dioxide, nano-titanium dioxide or nano-silicon carbide, or a combination of at least two thereof; The nanoparticles B include any one of nano-silicon dioxide, nano-titanium dioxide, nano-silicon carbide, nano-aluminum oxide, talc, magnesium stearate or magnesium oxide, or a combination of at least two thereof.
2. The polymer composite according to claim 1, characterized in that The mass ratio of the nanoparticles A to the nanoparticles B is (1.5-4):
1.
3. The polymer composite according to claim 1, characterized in that The polymer powder includes thermoplastic polymer powder and / or thermosetting polymer powder.
4. The polymer composite according to claim 3, characterized in that The polymer powder comprises a thermoplastic polymer powder.
5. The polymer composite according to claim 4, characterized in that The thermoplastic polymer powder includes any one of thermoplastic elastomer, polyamide, polyolefin, polymethacrylate, polycarbonate or polystyrene, or a combination of at least two thereof.
6. A method for preparing the polymer composite according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: After the polymer powder and the nanoparticles A are stirred and mixed for the first time, the mixed raw materials are stirred and mixed with the nanoparticles B for the second time, and sieved to obtain the polymer composite.
7. The preparation method according to claim 6, characterized in that: The first stirring and mixing time is 1-15 minutes.
8. The preparation method according to claim 6, characterized in that: The second stirring and mixing time is 1-6 minutes.
9. The preparation method according to claim 6, characterized in that: The sieving is performed through a sieve.
10. The preparation method according to claim 9, characterized in that: The mesh number of the sieve is 50-300 meshes.
11. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: The polymer powder and the nanoparticles A are stirred and mixed for the first time for 1-15 minutes, and then the mixed raw materials are stirred and mixed with the nanoparticles B for the second time for 1-6 minutes. Finally, the mixture is sieved with a sieve with a mesh size of 50-300 to obtain the polymer composite.
12. Use of the polymer composite according to any one of claims 1 to 5 in powder coating or 3D printing.
Citation Information
Patent Citations
Nylon composite powder material for selected laser sintering and preparation method of nylon composite powder material
CN108727814A
Nylon polymer powder heat-absorbing material and preparation method thereof
CN109929242A
Percarbonate bleach particles coated with partially hydrated crystalline aluminosilicate flow aid
CN1102954C
Treatment method for improving fluidity of thermoplastic polymer powder
CN107955191A